MIND MAPPING STRATEGY TO IMPROVE READING COMPREHENSION IN NARRATIVE SKILL OF STUDENTS AT MA AL-ISLAH DASAN AGUNG - Aristiawan, Danul; Herman, Herman (FKIP, Universitas Banten Jaya, 2024)
The objective of this research was to find out the implement of mind mapping techniques to improve students’ reading comprehension in narrative texts in eleven grade of MA Al-Islah Dasan Agung academic year 2023-2024. The research was conduct at Al-Islah Dasan Agung on 17 July – 03 August 2023. This research was carried in two classes, these are XI A as the experimental class consisted of 13 students and XI B as a control class consisted of 13 students. The research used quantitative method with quasi-experimental design. The data were gathered through test which were delivered into the pre-test and post-test. Based on the result of the research showed that mind mapping technique is improve students’ reading comprehension in narrative text, because the value of gained score (20.77) is higher than the control class (10.77). From the result of statistic hypothesis, has significance value 0.001. Based on the significance table is 0.05, meanings that 0.05 > 0.001. In other word the Alternative Hypothesis (Ha) is accepted and the Null Hypothesis (Ho) is rejected. Therefore, teaching reading comprehension of narrative text has improves through mind mapping technique